Monoamine oxidase B is elevated in Alzheimer disease neurons, is associated with γ-secretase and regulates neuronal amyloid β-peptide levels - Schedin-Weiss, Sophia; Inoue, Mitsuhiro; Hromadkova, Lenka; Teranishi, Yasuhiro; Yamamoto, Natsuko Goto; Wiehager, Birgitta; Bogdanovic, Nenad; Winblad, Bengt; Sandebring-Matton, Anna; Frykman, Susanne; Tjernberg, Lars O (Alzheimer's research & therapy, 2017)
BACKGROUND: Increased levels of the pathogenic amyloid β-peptide (Aβ), released from its precursor by the transmembrane protease γ-secretase, are found in Alzheimer disease (AD) brains. Interestingly, monoamine oxidase B (MAO-B) activity is also increased in AD brain, but its role in AD pathogenesis is not known. Recent neuroimaging studies have shown that the increased MAO-B expression in AD brain starts several years before the onset of the disease. Here, we show a potential connection between MAO-B, γ-secretase and Aβ in neurons. METHODS: MAO-B immunohistochemistry was performed on postmortem human brain. Affinity purification of γ-secretase followed by mass spectrometry was used for unbiased identification of γ-secretase-associated proteins. The association of MAO-B with γ-secretase was studied by coimmunoprecipitation from brain homogenate, and by in-situ proximity ligation assay (PLA) in neurons as well as mouse and human brain sections. The effect of MAO-B on Aβ production and Notch processing in cell cultures was analyzed by siRNA silencing or overexpression experiments followed by ELISA, western blot or FRET analysis. Methodology for measuring relative intraneuronal MAO-B and Aβ42 levels in single cells was developed by combining immunocytochemistry and confocal microscopy with quantitative image analysis. RESULTS: Immunohistochemistry revealed MAO-B staining in neurons in the frontal cortex, hippocampus CA1 and entorhinal cortex in postmortem human brain. Interestingly, the neuronal staining intensity was higher in AD brain than in control brain in these regions. Mass spectrometric data from affinity purified γ-secretase suggested that MAO-B is a γ-secretase-associated protein, which was confirmed by immunoprecipitation and PLA, and a neuronal location of the interaction was shown. Strikingly, intraneuronal Aβ42 levels correlated with MAO-B levels, and siRNA silencing of MAO-B resulted in significantly reduced levels of intraneuronal Aβ42. Furthermore, overexpression of MAO-B enhanced Aβ production. CONCLUSIONS: This study shows that MAO-B levels are increased not only in astrocytes but also in pyramidal neurons in AD brain. The study also suggests that MAO-B regulates Aβ production in neurons via γ-secretase and thereby provides a key to understanding the relationship between MAO-B and AD pathogenesis. Potentially, the γ-secretase/MAO-B association may be a target for reducing Aβ levels using protein-protein interaction breakers.
Keywords: Monoamine Oxidase; Animals; presenilin-1; sekretasy; Female; Amyloid beta-Peptides; axony; ženské pohlaví; Dendrites; transfekce; Transfection; synapse; dendrity; Cell Line, Transformed; lidé; amyloidní beta-protein; Mice; malá interferující RNA; neurony; Aged, 80 and over; mozek; Amyloid Precursor Protein Secretases; myši; monoaminoxidasa; Models, Molecular; Humans; regulace genové exprese; Neurons; Receptors, N-Methyl-D-Aspartate; molekulární modely; Male; Aged; Brain; RNA, Small Interfering; Alzheimer Disease; krysa rodu Rattus; receptory N-methyl-D-aspartátu; Alzheimerova nemoc; lidé středního věku; senioři nad 80 let; senioři; zvířata; mužské pohlaví; Gene Expression Regulation; Synapses; transformované buněčné linie; Middle Aged; Rats; Presenilin-1; Axons